1990
DOI: 10.1093/infdis/162.4.852
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Replication and Antigenic Properties of Human Herpesvirus 6 Strains

Abstract: The Z29 and U1102 strains of human herpesvirus 6 (HHV-6) were compared for their ability to replicate in fresh peripheral blood lymphocytes (PBL) and in continuous T cell lines. The replication of both strains in PBL was enhanced by mitogenic activation of cell growth. U1102 replicated in the continuous T cell lines, J JHAN and HSB-2, whereas no Z29 replication was observed in these cell lines as judged by infectious virus yields, the presence of viral antigens, and viral DNA replication. The two strains were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
67
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 0 publications
2
67
0
Order By: Relevance
“…There appear to be some growth differences between the groups, although these may be strain-specific. Comparative studies show growth of some isolates in different CD4 + T leukaemic cell lines: group A isolates in HSB2 cells, and group B isolates in MOLT3 cells (Wyatt et al, 1990;Ablashi et al, 1991;Schirmer et al, 1991;Chandran et al, 1992;Dewhurst et al, 1992). It has been suggested that the HHV-6 strain variant groups be reclassified (Schirmer et al, 1991), but the molecular basis of the grouping has not been determined and therefore it is not clear whether this represents variation between strains or new species.…”
Section: Introductionmentioning
confidence: 99%
“…There appear to be some growth differences between the groups, although these may be strain-specific. Comparative studies show growth of some isolates in different CD4 + T leukaemic cell lines: group A isolates in HSB2 cells, and group B isolates in MOLT3 cells (Wyatt et al, 1990;Ablashi et al, 1991;Schirmer et al, 1991;Chandran et al, 1992;Dewhurst et al, 1992). It has been suggested that the HHV-6 strain variant groups be reclassified (Schirmer et al, 1991), but the molecular basis of the grouping has not been determined and therefore it is not clear whether this represents variation between strains or new species.…”
Section: Introductionmentioning
confidence: 99%
“…HHV-6 was first isolated from the peripheral blood lymphocytes of patients with lymphoproliferative disorders and AIDS (34). HHV-6 isolates can be categorized as two variants, A (HHV-6A) and B (HHV-6B), on the basis of their in vitro growth properties, DNA restriction site polymorphisms, antigenicity, and host cell tropism (1,(3)(4)(5)45). HHV-6B is the causative agent of exanthem subitum (46).…”
mentioning
confidence: 99%
“…HHV-6B is the causal agent of exanthem subitum (62). The two variants can be differentiated on the basis of genomic polymorphism, antigenicity, and host cell tropism (1,3,7,61).…”
mentioning
confidence: 99%